STUDENTS’ BEHAVIORAL ENGAGEMENT IN LEARNING ENGLISH IN VOCATIONAL HIGH SCHOOL - Andhara Suci Elguanda; Siska Siska; Rika Afriyanti Afriyanti (Labor Program Studi Pendidikan Sosiologi, 2023)
The purpose of this study was to analyze student behavioral engagement about how students' behavior is related to academic assignments in tenth and twelfth grade of SMK N 1 Muara Bungo. So that students are interested in doing English assignments. in class X & XII SMK N 1 Bungo. The design of this research is descriptive qualitative. The sample of this research is class X AKL & XII MM2. The instruments used in this study were observation, using an observation checklist, field notes and videos. The results of this study are classified into three forms: persistence, focus, asking questions, contributing to class discussion. Based on the results of this study, researchers found that students had a consistent attitude of having behavioral engagement when doing assignments. Furthermore, in class students can be focused and contribute in class discussions, such as asking about instructions in doing assignments